Re-evaluation of the taxonomic status of four nominal, western Pacific species of tongue soles (Pleuronectoidei: Cynoglossidae: Cynoglossus), with redescription of C. joyneri Günther, 1878 - Luo, Hai-Rong; Kong, Xiao-Yu; Munroe, Thomas A. (Zootaxa, 2023)
Striking similarities in morphological characters and significant overlap in meristic features have resulted in different hypotheses regarding the taxonomic status of several nominal species of northwestern Pacific tongue soles of the genus Cynoglossus, including C. joyneri Günther, 1878, C. lighti Norman, 1925, C. tenuis (Oshima, 1927), and C. tshusanensis Chabanaud, 1951. Previous hypotheses have proposed that each taxon is a valid species; or that C. lighti and C. tshusanensis are junior subjective synonyms of C. joyneri; or that C. tenuis is a junior subjective synonym of either C. joyneri or C. lighti. Although several previous investigations concluded that C. lighti is a synonym of C. joyneri, names of both nominal species still appear in contemporary literature indicating that taxonomic status of these nominal species remains unresolved. To clarify the taxonomic status of these four nominal species, detailed study of morphological characters of 138 specimens collected from 22 localities in Japan and China, and re-examination of type specimens of three of these nominal species was conducted. The molecular barcodes of mitochondrial DNA from six representative specimens featuring morphological variation purportedly useful for distinguishing C. lighti from C. joyneri were also analyzed and then compared with sequences reported for C. joyneri in the literature. Lectotypes of C. joyneri and C. lighti differed in only two morphological characters (body depth and position of posterior tip of rostral hook relative to anterior margin of lower eye). However, when these two characters were examined in 138 recently collected non-type specimens, no differences were found among these nominal species. Our results do not support recognizing these as separate species. Results from genetic analyses also support recognizing only a single species among the material examined. Furthermore, overall similarities in morphological features between the holotype of C. tshusanensis and specimens of C. joyneri support recognizing C. tshusanensis as a junior subjective synonym of C. joyneri. Likewise, values for morphological features of C. joyneri examined in the present study also encompass the range of values reported in the original description of C. tenuis. This finding supports conclusions of previous studies that this nominal species is also a junior synonym of C. joyneri. Based on morphological and genetic evidence, we conclude that only a single species, C. joyneri, should be recognized among the four nominal species included in this study. Cynoglossus joyneri is re-described based on data from 492 specimens collected throughout nearly the entire range of the species.